KAJIAN TERJEMAHAN JAWA-ARAB PADA LIRIK LAGU NEMEN - Mukminin, Muhamad Saiful (Prosiding Seminar Nasional Bahasa Ibu; Vol 2 No 1 (2025): Prosiding Seminar Nasional Bahasa Ibu 2024/2025, 2025)
This study aims to describe the various techniques, methods, and ideologies used in translating the lyrics of the song Nemen from Javanese to Arabic. It adopts a descriptive qualitative paradigm with a product-oriented translation approach. The analyzed data consists of the transcription of the Nemen song lyrics in Javanese along with their Arabic translation. The Arabic translation of the song was obtained from the YouTube account Kampung Arab Music . Data collection was carried out using the listening and note-taking technique, while data analysis applied an interactive model consisting of data reduction, data presentation, and conclusion drawing. The findings reveal that eight translation techniques were applied in translating the song Nemen . The translation method of the Nemen song lyrics in the Javanese-Arabic context is more target language-oriented, making the underlying ideology lean toward domestication.